Analysis of 210Pb peak values at Mt. Cimone (1998–2011). (July 2015) - Brattich, E.; Hernández-Ceballos, M.A.; Cinelli, G.; Tositti, L.
Abstract: The present study analyses the peak 210 Pb activity concentrations observed all over the 1998–2011 period at the WMO-GAW high altitude site of Mt. Cimone (44.18N, 10.7E, 2165 m asl; Italy) in terms of meteorological conditions, links with other atmospheric species and population dose rate associated with this radiotracer. The highest 210 Pb events mainly occurred in the warm period and were associated with prolonged anticyclonic conditions, high temperatures, and low relative humidity values. A correlation with the seasonal pattern of the mixing height was also observed, suggesting the importance of thermal convection promoting uplift of warm air from the atmospheric boundary layer (ABL), transporting high concentrations of 222 Rn and thus 210 Pb. The main sources of high 210 Pb concentrations were identified by means of clusters of back-trajectories applied at three different heights. Sources located at east (central Europe), at west (Spain and France) and south (northern Africa) of Mt. Cimone were distinguished. The clusters obtained at the three heights were compared in order to study the extent between ABL and free troposphere during the highest 210 Pb events: a wide influence of the strong coupling among atmospheric vertical layers on 210 Pb activity concentrations increases was demonstrated. The annual effective dose from the potential inhalation of this radionuclide during the peak concentration episodes was also calculated. The average dose increase during the selected events represents only a small fraction of the total dose from all sources; these results are nevertheless useful for providing information on natural background dose contribution from inhalation which is required for the accurate assessment of dosimetric conditions in the case of nuclear emergencies. Highlights: High altitude station representative of the Southern-European free-troposphere. Sources of the peak 210 Pb events at Mt. Cimone at east, west and south of the site. Peak 210 Pb linked with high pressures and temperatures, and low relative humidity. Influence of the strong coupling among atmospheric vertical layers on 210 Pb. Average dose increase during peaks only small fraction of the total dose.